(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This study examined the relationship between cultural tourism and community development of selected communities in Akwa Ibom State, Nigeria. The study adopted a cross-sectional survey of quasi-experimental research design. The study population considered were tourists that visits the attractions sites in the communities and the sample size of 384 was determined using Freund and William sample size determination method while statistical analysis was conducted with Pearson’s product moment correlation with the aid of SPSS. The study revealed that cultural tourism has a significant correlation with community development. The study recommended that communities should harness their cultural resources and package them for commercial purposes capable of attracting tourists to significantly contribute to